2016
DOI: 10.1088/1475-7516/2016/07/006
|View full text |Cite|
|
Sign up to set email alerts
|

Brans-Dicke inflation in light of the Planck 2015 data

Abstract: We study inflation in the Brans-Dicke gravity as a special model of the scalar-tensor gravity.We obtain the inflationary observables containing the scalar spectral index, the tensor-to-scalar ratio, the running of the scalar spectral index and the equilateral non-Gaussianity parameter in terms of the general form of the potential in the Jordan frame. Then, we compare the results for various inflationary potentials in light of the Planck 2015 data. Our study shows that in the Brans-Dicke gravity, the power-law,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 120 publications
(245 reference statements)
2
30
0
Order By: Relevance
“…f → 0, and σ → 0 (i.e. spatially flat Friedmann-Robertson-Walker (FRW) universe), the model is reduced to that of the [54], [55] and [56]. Moreover, in the limit F (R, φ) = R and ω(φ) = 1 it is reduced to [41].…”
Section: Anisotropic Inflation In Scalar-tensor Gravitymentioning
confidence: 99%
“…f → 0, and σ → 0 (i.e. spatially flat Friedmann-Robertson-Walker (FRW) universe), the model is reduced to that of the [54], [55] and [56]. Moreover, in the limit F (R, φ) = R and ω(φ) = 1 it is reduced to [41].…”
Section: Anisotropic Inflation In Scalar-tensor Gravitymentioning
confidence: 99%
“…We need just to have b > 0 due to having the end of inflation. Figure 5 shows that, in contrary to the result of quartic potential in both the Einstein [19] and standard BD gravity [20], the result of the model (22) for 0.09 ≤ ω 0 ≤ 1.2 lies inside the 68% CL region of Planck 2015 TT,TE,EE+lowP data [19]. Also the running of the scalar spectral index predicted by the model (22) is favored by the Planck 2015 data, see Fig.…”
Section: B Exponential Generalized Bd Parametermentioning
confidence: 84%
“…Also, the prediction of quartic potential in the standard BD gravity is disfavored by the Planck 2015 results [20]. In [36], it was shown that in the context of standard BD theory, the potential (20) can justify the late-time accelerated phase of the universe. It was pointed out that the scalar field ϕ in BD gravity can play the role of the dynamical Λ and describe the missing energy.…”
Section: Quartic Potential and Generalized Bd Parametermentioning
confidence: 99%
See 1 more Smart Citation
“…A remarkable feature of this induced affine inflation is that, in addition to the nearly scale invariant spectrum of perturbations, it predicts a unique spectral index due to the existence of a unique frame set by a unique metric tensor. This feature is an important advantage compared to the induced inflation based on action (1), which suffers from Jordan-Einstein frame ambiguity (see the old and recent works [4][5][6][7][8][9][10][11][12][13]). Nevertheless, here we emphasize that, as in the induced gravity inflation, the observable quantities, namely the spectral index and the tensor-to-scalar ratio, are both sensitive to the nonminimal coupling parameter and can hardly stay in the observational bounds.…”
Section: Introductionmentioning
confidence: 99%